Survei Kondisi Sarana Dan Prasarana Pembelajaran Pendidikan Jasmani Sekolah Dasar Negeri di Kecamatan Kajoran Kabupaten Magelang Tahun 2022 (Universitas Negeri Semarang, 2022)
This research was motivated by the unknown conditions and conditions of physical education learning facilities and infrastructure in public elementary schools in Kajoran District, Magelang Regency. The purpose of this study is to determine the condition and existence of Physical Education learning facilities and infrastructure in elementary schools in Kajoran District, Magelang Regency. The research method used is a survey with a quantitative descriptive approach. The research location is in Magelang Regency with a research target of 10 elementary schools in Kajoran District, Magelang Regency. The data collection technique uses the quota sampling technique. The instruments used used observations, interviews with principals and physical education teachers, observation sheets and documentation. Data collection includes the number of tools, the number of tools, the number of facilities, the condition of the tools, the condition of the tools and the condition of the facilities. The analysis used is percentage by classifying the types of data obtained from observation sheets and grouped. Based on the results of research on the condition and existence of Physical Education learning tools in Elementary Schools, Kajoran District, Magelang Regency, from 10 schools, there is 1 school that is included in the excellent category with a percentage of 10%, namely SDN Mangunrejo. Then there are 2 schools in the good category with a percentage of 20% including SDN Sutopati 1 and SDN Sukomulyo. Then there are 3 schools in the medium category with a percentage of 30% including SDN Ngargosari, SDN Ngendrosari, SDN Sidorejo. And there are 4 schools in the less category with a percentage of 40% including SDN Bambusari, SDN Banjaragung, SDN Lesanpuro, SDN Kuwaderan 1. The conclusion in this study is that the facilities and infrastructure in elementary schools in Kajoran District, Magelang Regency, many schools are still in the category of lacking. The advice given by the researcher is so that the Magelang Regency government pays more attention to the facilities and infrastructure in the Kajoran District Elementary School and also physical education teachers can maintain and modify the facilities and infrastructure in the school.